Effect of supplementation with chokeberry juice on the inflammatory status and markers of iron metabolism in rowers - Skarpanska-Stejnborn, A.; Basta, P.; Sadowska, J.; Pilaczynska-Szczesniak, L. (Journal of the International Society of Sports Nutrition, 2014)
Background: The aim of this study was to analyze the effect of supplementation with chokeberry (Aronia melanocarpa) juice on the levels of pro-inflammatory cytokines, hepcidin, and selected markers of iron metabolism in rowers subjected to exhaustive exercise.